The Capability of Extension Agents in Disseminating Climate Change Information in Delta State Nigeria - Remigius Ikechukwu Ozioko; Kelvin Chinedu Eze; Abigail Ngozi Emordi; David John Okoronkwo; Cynthia Ebere Nwobodo (Journal of Agricultural Extension, 2022)
The study assessed the capacity for outreach to farmers on climate change among extension agents in Delta State, Nigeria. It identified; the capacity for outreach of extension agents to farmers; existence of linkage on cc; sources of information on cc; constraints to building capacities for outreach; and strategies to strengthen capacities. A multi-stage technique was used in selecting 60 respondents. Mean, percentage, frequency were used for analysis. Findings showed that 23.3% of the respondents indicated existence of training on cc. Also, 20% of the agents had practical learning experience on cc adaptation. All agents (100%) acknowledged no investment in infrastructural development on cc within the last three years. Lack of human resources (M= 3.30), training programmes on cc (M= 3.23)  were constraints. Strategies to strengthen capacity included; organization of seminars, workshops (M= 3.58), proper staffing (M= 3.57), provision of incentives (M= 3.55), among others. The agents had knowledge of cc and its accompanied effects; but operational environment is characterized by inadequate facilities for outreach. Government and development agencies should commit more human, financial and technical resources to extension delivery in Delta State in order to boost production and address climate challenges.